Analysis of Factors Associated with the Incidence of Dengue Hemorrhagic Fever (DBD) - Astuti Astuti; Irfansyah Baharuddin Pakki; Iwan Muhamad Ramdan (Indonesian Journal of Global Health Research, 2025)
Dengue fever is still a public health problem worldwide, especially in tropical and subtropical regions. Data from around the world shows that Asia ranks first in the number of Dengue Fever sufferers each year. The purpose of this study was to determine the factors that affect the incidence of Dengue Fever (DHF) in the work area of BLUD Puskesmas Sangatta Utara, Kecamatan Sangatta Utara, Kabupaten Kutai Timur. This study used a case-control design, with 115 positive cases of DHF and 115 control cases in the work area of BLUD Puskesmas Sangatta Utara, East Kutai Regency, making a total of 230 samples. The data collection techniques included a preparation stage (obtaining research permits and conducting a preliminary study), followed by an implementation stage (collecting respondent data, sorting samples according to criteria into two groups, filling out questionnaires, and collecting research instruments). This study found a significant association with the incidence of DHF in the following variables: knowledge (p < 0.001) OR 0.061, daytime activity (p < 0.001) OR 2.878, mosquito nest eradication efforts (p < 0.001) OR 0.118, and the habit of hanging used clothes in the house (p < 0.001) OR 8.576. It can be concluded that the habit of hanging used clothes in the house is the most dominant variable associated with the incidence of DHF in the work area of BLUD Puskesmas Sangatta Utara (Odds Ratio Exp(β) = 89.297).